PENGARUH LINGKUNGAN KELUARGA TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI SD ISLAM AS-SALAM DAN DAARUL FIKRI MALANG - Anisa Anisa (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
This study aims to ascertain the importance of the family environment on the religious character of students in As-salam Islamic Elementary School and Daarul Fikri Islamic Elementary School. This study is a survey research with a quantitative approach, data collected by questionnaire techniques, interviews, and documentation. The population is 128 people with a sample of 97 respondents consisting of 49 class V and 48 class V1. Data analysis techniques include Outer Model, Inner Model, and Bootstrapping. The results revealed that there was no significant positive effect between the family environment on a religious character with a p-value of 0.049 <0.05. The level of influence of the family environment on a religious character is 0.045 or with a value of a precentage 4,5%.